The Effectiveness of Diabetes Self-Management Education on Improving the Self-Efficacy of Diabetes Mellitus Patients in the Puskesmas Kota Langsa - Z, Zulkarnaini; E, Elfida; I, Idwar; Hayani, Nora; A, Azwarni (Buletin Farmatera, 2022)
Abstract: Diabetes Mellitus (DM) is one of the chronic diseases that every year the number of sufferers is increasing in various parts of the world. The common knowledge of diabetics regarding their disease causes them to be unable to properly carry out self-care, so their blood sugar levels are not controlled. Diabetes is also one of the comorbidities that cause death in Covid-19 patients. The purpose of this study was to test the effectiveness of Diabetes Self Management Education (DSME) in improving the self-efficacy of type 2 diabetes mellitus patients in the work area of the Langsa Kota Health Center. The method used quasi-experiment and design was pre-test and post-test with a control group design, with 25 respondents for each group. The study was conducted from June 7 August 7, 2021, in the working area of the Langsa Kota Health Center. Data collection was carried out using questionnaires, the implementation of comprehensive education, measurement of blood sugar levels, and taking into account research ethics. The results of the writing were obtained by the majority of female respondents in the early adult age category, the majority of whom had diabetes over 10 years old. The paired t-test found significant differences in the intervention group after receiving DSME education compared to the control group. Education was conducted intensively in the intervention group, which discussed knowledge of DM, diet, physical exercise, and stress management. It is hoped that puskesmas can adopt DSME as a reference in educating the public, especially people with type 2 diabetes mellitus.Keywords: Diabetes Self Management Education, Self Efficacy, DSME